Sistem Pendukung Keputusan untuk Optimalisasi Pemilihan Agen Penjualan Menggunakan Metode Entropy dan Multi Attribute Utility Theory - Nurnaningsih, Desi; Setiawansyah, Setiawansyah (CV. Keranjang Teknologi Media, 2024)
Optimizing the selection of sales agents is a strategic approach that aims to improve efficiency and performance in the company's supply chain. The problem that occurs in this study is that the assessment of sales agents based on networks and personal connections can often lead to non-objectivity and reduce transparency in the selection process, and there is no model that can make judgments in selecting the best sales agents. The purpose of this study is to optimize the selection of sales agents by applying the Entropy method for weighting criteria and the MAUT method to produce the selection of the best sales agent based on predetermined criteria, so that it will be a recommendation in determining the best sales agent. The purpose of this study is to optimize the selection of sales agents by applying the Entropy method for weighting criteria and the MAUT method to produce the selection of the best sales agent based on predetermined criteria, so that it will be a recommendation in determining the best sales agent. The results of the alternative ranking of the selection of the best sales agent showed that rank 1 with a final value of 0.8491 was obtained by Various Agents, rank 2 with a final value of 0.6737 was obtained by Mekar, rank 3 with a final value of 0.6401 was obtained by Andalas Agents.